2020
DOI: 10.31093/jraba.v5i1.206
|View full text |Cite
|
Sign up to set email alerts
|

Improving Financial Performance Through Islamic Corporate Social Responsibility and Islamic Corporate Governance

Abstract: Penelitian ini bertujuan untuk menganalisis dan menguji secara empiris Islamic corporate social responsibility dan Islamic corporate governance dalam meningkatkan kinerja keuangan Bank Umum Syariah. Populasi penelitian ini adalah seluruh Bank Umum Syariah yang terdaftar di Bank Indonesia tahun 2013- 2018 yang berjumlah sebanyak 72 Bank Umum Syariah. Sampel penelitian yang digunakan dalam penelitian ini berdasarkan teknik purposive sampling sebanyak 60 Bank Umum Syariah. Semua data dalam variabel ini akan di an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…This will impact increasing the support of stakeholders and the community to BUS and will make it easier for BUS to carry out company operational activities, which will affect the improvement of BUS performance. This is in line with the results of research (Wijayanti & Setiawan, 2022), (Indriastuti & Najihah, 2020) and (Wardiwiyono & Jayanti, 2021) which states that social reporting has been found to harm ROA. However, it has a positive impact on MTBV, and Tobin's Q.…”
Section: Hypothesissupporting
confidence: 91%
See 1 more Smart Citation
“…This will impact increasing the support of stakeholders and the community to BUS and will make it easier for BUS to carry out company operational activities, which will affect the improvement of BUS performance. This is in line with the results of research (Wijayanti & Setiawan, 2022), (Indriastuti & Najihah, 2020) and (Wardiwiyono & Jayanti, 2021) which states that social reporting has been found to harm ROA. However, it has a positive impact on MTBV, and Tobin's Q.…”
Section: Hypothesissupporting
confidence: 91%
“…(Syurmita & Fircarina, 2020) If the company has interests and responsibilities to stakeholders, the company's performance will be maximized optimally because, indirectly, ICSR is the company's most significant achievement that must be fulfilled. Research conducted by (Indriastuti & Najihah, 2020) and (Wardiwiyono & Jayanti, 2021) stated that ICSR proxied by ISR disclosure has a positive and significant influence on the financial performance of Islamic banks. In contrast to the results of previous studies, (Xue et al, 2023) found that voluntary CSR disclosure negatively affects profitability.…”
Section: Introductionmentioning
confidence: 99%
“…The link between this concept and Islamic Corporate Social Responsibility is the perspective of resources by the company, as a mandate from God that is inherent in a responsibility. Indriastuti & Najihah, 2020) argued that corporate social activity is a form of compliance and responsibility of the company owner for his beliefs, in order to maintain and share with the surrounding. It is a way to contribute to the good of all those who need it.…”
Section: Literature Review Agency Theorymentioning
confidence: 99%
“…Many central banks worldwide promote the optimization of Good Corporate Governance (GCG) in all institutions. GCG can enhance transparency and financial management performance in Sharia banking, specifically in operational activities that directly involve Sharia banking stakeholders and clients (Cholisoh & Hadziq, 2021;Indriastuti & Najihah, 2020;Khairiah & Inayah, 2023). Additionally, GCG is implemented to reduce the likelihood of financial report manipulation and Sharia banking performance degradation.…”
Section: Figure 1 Distribution Of Sharia Banking Assets By Country In...mentioning
confidence: 99%